Levantamiento geológico – estructural de la vía antigua a Cuenca, abscisas km 21+150 hasta km 26+150 perteneciente a las parroquias San Lucas – Santiago, cantón y provincia de Loja - Sarango Ordoñez, Alex Gonzalo (2024)
The present research degree carried out the geological-structural survey of the old road to Cuenca, between the abscissa km 21+150 up to km 26+150, considering a study strip of 250 m per side, belonging to the San Lucas and Santiago parishes, from the Loja canton and province. The study area has a total of 2,329 km2 and a very irregular topography with elevations from 2015 to 2325 m.a.s.l. with a difference in height of 310 m, it presents mountainous land relief with predominantly tilt slopes (15° - 35°) and steep (35° - 55°) slopes. For the local geology survey, the outcrop mapping method was used to determined that the study area is part of an extensive intrusive body known as San Lucas Batholith, made up of four lithological units: Granite, Granodiorite, Diorite and Rhyolite, as well as alluvial and colluvial deposits. Granodiorite is the predominant unit, it extends from the central area to the north, occupying an area of 1,10 km2, made up of granodiorite with biotite. The Granito unit is the second largest, it extends from the south to the central zone, taking up an area of 0,056 km2 and is characterized by the presence of granite. The Diorite unit is located to the southeast, occupying an area of 0,056 km2, made up of weathered diorite, which is in inferred contact with the Granite unit; and the Rhyolite unit located in the central west, covers an area of less than 0,021 km2 made up of jointed rhyolites, this unit overlies the Granite unit. Moreover, in the southeast and northeast, some subvertical andesite dykes were identified in the Granite and Granodiorite units. Structurally, the study area is controlled by ten faults: an inferred regional fault with NW-SE direction; one observed normal fault with NW-SE direction and two microfaults with NE-SW direction; furthermore six photointerpreted faults with NE-SW preferential direction. In addition, there are 27 families of inclined, subhorizontal and subvertical type tectonic joints, the majority have an NW-SE dip direction. Keywords: local geology, lithological units, faults, joints.